PhDHS Is Involved in Chloroplast Development in Petunia - Liu, Juanxu; Chang, Xinlei; Ding, Beibei; Zhong, Shan; Peng, Li; Wei, Qian; Meng, Jie; Yu, Yixun (Frontiers in Plant Science, 2019)
Deoxyhypusine synthase (DHS) is encoded by a nuclear gene and is the key enzyme involved in the post-translational activation of the eukaryotic translation initiation factor eIF5A. DHS plays important roles in plant growth and development. To gain a better understanding of DHS, the petunia (Petunia hybrida) PhDHS gene was isolated, and the role of PhDHS in plant growth was analysed. PhDHS protein was localized to the nucleus and cytoplasm. Virus-mediated PhDHS silencing caused a sectored chlorotic leaf phenotype. Chlorophyll levels and photosystem II activity were reduced, and chloroplast development was abnormal in PhDHS-silenced leaves. In addition, PhDHS silencing resulted in extended leaf longevity and thick leaves. A proteome assay revealed that 308 proteins are upregulated and 266 proteins are downregulated in PhDHS-silenced plants compared with control, among the latter, 21 proteins of photosystem I and photosystem II and 12 thylakoid (thylakoid lumen and thylakoid membrane) proteins. In addition, the mRNA level of PheIF5A-1 significantly decreased in PhDHS-silenced plants, while that of another three PheIF5As were not signifilantly affected in PhDHS-silenced plants. Thus, silencing of PhDHS affects photosynthesis presumably as an indirect effect due to reduced expression of PheIF5A-1 in petunia.